Fair Value of Pancasila in the Framework of Criminal Code Renewal - Ginting, Yuni Priskila; Wartoyo, Franciscus Xaverius (Law Review, 2023)
Pancasila is the ideological foundation of the Indonesian state that guarantees the unity and integrity of Indonesians entering the era of globalization. Current Indonesian criminal law is obsolete because it does not consider Indonesia's philosophical, sociological, and cultural values and does not follow the changing mindset of modern criminal law. Social policy must be woven into and placed in a carefully integrated social plan, especially to prevent unwanted access related to crime. Indonesian criminal law will continue to apply colonial values that are not based on Pancasila values. The codification of laws that live in society is regulated specifically for public awareness of the potential for the law that can be used as a reference for regional regulations. The basic idea of Pancasila's balance is based on the religious moral paradigm, the human paradigm, the nationality paradigm, the democracy and wisdom paradigm, and the social justice paradigm. Justice is an abstract value that must be realized in the form of legal norms to realize these values in social life without ignoring religious law, customary law, and Western law. This does not correspond to the value contained in Pancasila.